Szent Imre Kertváros. Egy város-antropológiai kutatás vázlata - Teplán, István (Tér és Társadalom, 1990)
The present paper is based on the assumption that the one-time spirit of a place leaves the most telling evidence on the material cultures it once created, and of all these, architectural objects are the most accessible. Every building, even the simplest one, carries with it communicative, connotatitive signs beyond the primary, denotative (functional) meaning. By analyzing these signs, we can tap a pool of information which could, in the author's view, provide important additional data and complement the traditional analyses of urban studies and historical economy. The area chosen, St. Emeric Garden City, was an individual region of Budapest. Althought it had no two identical buildings, a homogeneous intent and spirit were apparent–the manifestitation of some kind of style which could not be called purely architectural. The area in question was previosly called „St. Emeric Colony", and later was also known as the „Officials' Colony"; now its inhabitants mostly refer to it as „Garden City". Geographically, it is located in the outskirts of Budapest, in the suburb of Pestlőrinc. The idea of building the settlement was introduced in 1920. "The Pestlőrinc Garden Estate Home of Civil Servants" was founded in October 1920 with 250 members, a number that later grew to 800, settling finally (around 1930) at about 280-300. A lot of non-refugee joined the originally mostly Transylvanian and North- and South-Hungarian members. The majority of the owners of the houses belonged to the so-called „Christian middle class". In the little world of this garden city, we see an almost urban life which is a mixture of bourgeois and gentry elements. The residents wishing to defend their lost world in their new neighbourhood, reestablished their beloved but sometimes old-fashioned little society based on values which they cherished but which were fast disappearing. This settlement was on the edge of the modern city, both time and space representing the contradictory social development of interwar Hungary.